Design of a Digital Clock Application Using the Atmega 8535 Microcontroller Based Alarm - Adi Tiarno Manik (Bahasa Indonesia, 2020)
Seeing the reality that is happening in schools where alarms are needed as a sign or information about the start of lessons, breaks, ends of lessons until coming home from school. This is often done manually. This research was conducted to replace the manual tool with automatic equipment through the design of a digital clock using a Real Time Clock IC that uses an ATMega 8535 microcontroller as the controller of the entire circuit. In this system, a buzzer is used as an alarm and a seven segment as a time display. The time that is the reference in the digital clock is set at the beginning of the use of this digital clock into the RTC IC via a push button so that the microcontroller will retrieve the time data at a certain memory address. Based on the test results, starting from the time set, alarm set, the selection of the alarm sound until the activation of the alarm sound can be controlled by the microcontroller. Overall this system can function as designed.